Muamalah Fiqh Analysis of the Use of Shopee Paylater: (Case Study on the Shopee Application) - Ahmadi, Mirzam Arqy; Khasanah, Uswatun; Faza, Putri Rizqya; Adelia, Tifani; Satiti, Saltsa Woro Ayu; Agustina, Alya; Pratama, Shaka Yudha; Fanny, Dhevan Muhammad (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2024)
In the era of advancing technology, online services have become a solution to meet human needs by facilitating access to various aspects of life. One renowned online shopping platform is Shopee, Providing an extensive array of items, ranging from food and apparel to household appliances.. Shopee users are familiar with the "Pay Later" feature, or SpayLater, allowing payment for purchased items without an immediate settlement, known as a credit system with applicable terms and conditions. This research utilizes qualitative data obtained through documentation and literature studies from various sources, primarily secondary sources such as journals, articles, reports, and information related to the review of Islamic Jurisprudence (Fiqh) and fundamental principles of Fiqh Muamalah concerning credit systems in buying and selling transactions. The aim of this study is to evaluate the Fiqh Muamalah perspective on the credit system offered by Shopee through the "SPayLater" feature. The qualitative data obtained through documentation and literature studies from various secondary sources such as journals, articles, reports, and related information reveal that the use of the SPayLater credit system, from the perspective of Fiqh Muamalah, is considered permissible (mubah). This is because the contract executed during the transaction is evidently clear through the agreement made between the seller and the buyer during the execution of the offer and acceptance (ijab and qabul), along with the agreed-upon additional fees for deferment in the SPayLater credit system. However, the research also highlights that the use of SPayLater becomes impermissible (haram) when it involves the element of interest that must be paid by the buyer if not settled within the specified timeframe. In this case, SPayLater users are subject to a 5% interest charge on the total bill, conflicting with the fundamental principles of Fiqh Muamalah. Thus, although SPayLater may be acceptable in terms of the contract and agreement, the presence of interest in the payment system can be controversial from the perspective of Fiqh Muamalah, as this practice is considered usury, which is prohibited in Islam.